Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.14260/jemds/1550
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical Presentation and Management of Abdominal Tuberculosis in a Tertiary Care Hospital

Abstract: BACKGROUND:Ovarian torsion presents as acute abdominal pain and early surgical management is required to prevent further adnexal damage. It accounts for 3% of all cases of acute abdominal pain in adult women. As signs and symptoms can mimic other acute abdominal conditions, the preoperative diagnosis often remains a challenge for primary care physicians. AIMS AND OBJECTIVES: To study the characteristics of adnexal torsion and factors influencing adnexal preservation. MATERIAL AND METHODS: All 14 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…These results are consistent with the findings of Darbari A et al 2 (58%), Krishnanand et al 9 (54.8%), Tripathi PB et al 10 (55.4%), Zea MI et al 11 (64%), Saaiq M et al 12 (61.37%), Shimy GG et al 13 (45.56%), Islam MB et al 14 (75%) and Rabbi ANMA et al 15 (54.54%).…”
Section: Age-wise Distribution Of Gitb Casessupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with the findings of Darbari A et al 2 (58%), Krishnanand et al 9 (54.8%), Tripathi PB et al 10 (55.4%), Zea MI et al 11 (64%), Saaiq M et al 12 (61.37%), Shimy GG et al 13 (45.56%), Islam MB et al 14 (75%) and Rabbi ANMA et al 15 (54.54%).…”
Section: Age-wise Distribution Of Gitb Casessupporting
confidence: 87%
“…Previous authors have reported intestinal obstruction ranging from 9.3% (Ibrahim et al 22 ) to 66.65% (Krishnanand et al 9 ). Intestinal obstruction occurs mainly due to narrowing of the lumen by hyperplastic caecal tuberculosis by strictures of the small intestine, which are commonly multiple or by adhesions.…”
Section: Clinical Presentationmentioning
confidence: 94%
“…Primarily, tuberculosis of intestine without antecedent or associate with pulmonary tuberculosis is fairly common. 6,7 The reported incidence of gastrointestinal tuberculosis secondary pulmonary tuberculosis fall in wild range from 1 to 9% gastrointestinal tract involved in majority cases of abdominal tuberculosis, only 15 to 20% have concomitant pulmonary tuberculosis, thus common ending of disease with disease manifestation and present with varied complication remains a challenge to the diagnosis and skill and integrity of the surgeon. Although, abdominal tuberculosis is common diagnosis and it is difficult as it often not possible to get microorganism for confirmation of infection.…”
Section: How To Cite This Articlementioning
confidence: 99%